Sarawak Digital Economy and The Organisational Sensemaking Process of CSR: A Conceptual View - Ahmad, Dayang Aizza Maisha Abang; Ahmad, Jamilah; Saad, Suriati (Penerbit UKM, 2020)
The Sarawak Digital Economy (SDE) is an initiative that was recently implemented by the Sarawak Government in its effort to turn Sarawak into a high-income and developed State by year 2030. Based on this vision, the Sarawak Government has addressed the critical need for an effective collaboration with the local organisations. Since the early 2000s, Corporate Social Responsibility (CSR) has become one of the innovative mechanism used by governments of various localities to work with local organisations for the interest of the community. In some regions, CSR has been widely used as a platform to cope with the social challenges such as unemployment and poverty. Based on these common practices, it is reasonable for this study to anticipate the likelihood for similar mechanism of collaboration to take place in Sarawak especially in respective to the joint effort required between the Sarawak Government with the local organisations to ensure successful implementation of SDE. This perspective in turn, puts into emphasis the potential ‘trigger’ effect that SDE may impose on the affected local organisations, including its CSR activities and orientation. Henceforth, the need for this study to view the development and implementation of CSR in an organisation as a sensemaking process. In this respect, this article takes the pioneering step to put present a conceptual view of the organisational CSR sensemaking process, and rationalise as to how CSR should be analysed especially in the scope of Sarawak’s current economic plan and direction.